Increased nitrate intake from beetroot juice does not alter soluble cellular adhesion molecules and circulating inflammatory cytokines in individuals with treated hypertension: a randomised, controlled trial. Issue 23 (11th November 2022) - Raubenheimer, Kyle; Liu, Alex H.; Koch, Henrietta; Bosio, Erika; Bondonno, Nicola P.; Matthews, Vance; Sim, Marc; Blekkenhorst, Lauren; Woodman, Richard J.; Murray, Kevin; Croft, Kevin; Neubauer, Oliver; et al.
Abstract : Increasing dietary nitrate consumption over 7 days is not effective in reducing soluble inflammatory mediators in individuals with treated hypertension. Abstract : Dietary nitrate, found predominantly in green leafy vegetables and other vegetables such as radish, celery, and beetroot, has been shown to beneficially modulate inflammatory processes and immune cell function in animals and healthy individuals. The impact of increased nitrate intake on soluble inflammatory mediators in individuals with hypertension is unclear. We assessed whether the daily consumption of dietary nitrate via beetroot juice for 1-week lowered levels of circulating inflammatory markers in men and women with treated hypertension. Twenty-seven male and female participants were recruited to a randomized, placebo-controlled, double-blind crossover trial. The effects of 1-week intake of nitrate-rich beetroot juice versus 1-week intake of nitrate-depleted beetroot juice (placebo) were investigated. Plasma concentrations of circulating soluble adhesion molecules (ICAM-1, VCAM-1, CD62E, CD62P), inflammatory cytokines (IL-1β, IL-6, IL-10, IL-12p70, TNF-α) and chemokines (IL-8, MCP-1) were measured by multiplex flow cytometric bead array in samples collected on day 7 of each intervention period. Other outcomes included alterations in nitrate metabolism assessed by measuring nitrate and nitrite concentrations in plasma, saliva, and urine. One week of beetroot juice did not alter levels of the soluble adhesion markers or cytokines assessed. A 7-fold increase in salivary nitrite, an 8-fold increase in salivary nitrate, a 3-fold increase in plasma nitrate and nitrite, and a 4-fold increase in urinary nitrate and nitrite compared to the placebo was observed ( p < 0.001 for all comparisons). Increasing dietary nitrate consumption over 7 days is not effective in reducing soluble inflammatory mediators in individuals with treated hypertension. This trial was registered at anzctr.org.au as ACTRN 12613000116729.